Tailoring microbial redox with alternating current for efficient mineralization of refractory organic nitrogen compounds in wastewater - Ye Yuan; Xucui Qian; Lulu Zhang; Wanxin Yin; Tianming Chen; Zhaoxia Li; Cheng Ding; Bo Wang; Bin Liang; Aijie Wang; Yang Liu; Fan Chen (npj Clean Water)
Abstract Traditional biological wastewater treatment struggles to efficiently remove refractory organic nitrogen compounds (RONCs). This study demonstrates the potential of alternating current (AC)-driven bioelectrodes for deep mineralization of nitrobenzene (NB) by coupling in situ reduction and oxidation reactions. Sine-wave AC bioelectrodes overcome the limitations of direct current (DC) systems, achieving 97.6% NB reduction, 90.9% intermediate mineralization, and 80.8% total nitrogen removal while reducing energy consumption by 22.3%. AC stimulation enhances biofilm formation and bidirectional electrocatalytic activity, leading to higher biomass and electron utilization efficiency. Multi-omics analysis shows enrichment of functional microbial consortia involved in NB reduction, aromatic compound oxidation, ammonia oxidation, nitrate/nitrite reduction, and electron transfer, with upregulated enzyme gene expression. Carbon metabolites from catechol meta-cleavage support nitro-reduction, denitrification, and cell viability without external carbon sources. Nitrification-denitrification is the primary pathway for inorganic nitrogen removal. This AC bioelectrode offers an efficient, low-carbon solution for RONC mineralization in wastewater.